A Sign Language Learning Video for Science Terminology on the Topic of States of Matter and Their Changes for Kolok Students - Kadek Tedy Iwan Suryawan; Putu Nanci Riastini; Luh Sri Surya Wisma Jayanti (Jurnal Media dan Teknologi Pendidikan, 2026)
Science learning in elementary schools often faces challenges in conveying complex scientific terminology, particularly for deaf students who require visual support and sign language to understand abstract concepts. The limited availability of learning media that can bridge the communication needs of kolok students with science content further exacerbates this issue. This study aims to develop and evaluate the feasibility and practicality of a sign language–based instructional video media using kolok vocabulary on the topic of states of matter and their changes for fourth-grade elementary students. This study employs a development research design using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects include material experts, media experts, teachers, and students. Data were collected through relevance scales and questionnaires, with instruments in the form of validation sheets and user response questionnaires, and were analyzed using qualitative and descriptive quantitative techniques. The results indicate that the developed media demonstrates a very high level of validity based on expert evaluations and a very good level of practicality based on responses from teachers and students. Therefore, the sign language–based instructional video media using kolok vocabulary is considered valid and practical for use in science learning. The implications of this study highlight the importance of developing inclusive learning media based on students’ needs to enhance conceptual understanding and scientific literacy.